Differential bioaccumulations and ecotoxicological impacts of metal-oxide nanoparticles, bulk materials, and metal-ions in cucumbers grown in sandy clay loam soil. (15th November 2021) - Ahmed, Bilal; Rizvi, Asfa; Syed, Asad; Jailani, Afreen; Elgorban, Abdallah M.; Khan, Mohammad Saghir; AL-Shwaiman, Hind A.; Lee, Jintae
Abstract: Expanding applications of metal-oxide nanoparticles (NPs) and increased environmental deposition of NPs followed by their interactions with edible crops threaten yields. This study demonstrates the effects of aging (45 days in soil) of four NPs (ZnO, CuO, Al2 O3, TiO2 ; 3.9–34 nm) and their corresponding metal oxide bulk particles (BPs; 144–586 nm) on cucumbers ( Cucumis sativus L.) cultivated in sandy-clay-loam field soil and compares these with the phytotoxic effects of readily soluble metal salts (Zn 2+, Cu 2+, and Al 3+ ). Data revealed the cell-to-cell translocations of NPs, their attachments to outer and inner cell surfaces, nuclear membranes, and vacuoles, and their upward movements to aerial parts. Metal bioaccumulations in cucumbers were found in the order: (i) ZnO-NPs > ZnO-BPs > Zn 2+, (ii) CuO-NPs > CuO-BPs > Cu 2+, (iii) Al 3+ > Al2 O3 -NPs > Al2 O3 -BPs and (iv) TiO2 -NPs > TiO2 -BPs. Aging of NPs in soil for 45 days significantly enhanced metal uptake (P ≤ 0.05), for instance aged ZnO-NPs at 1 g kg −1 increased the uptake by 20.7 % over non-aged ZnO-NPs. Metal uptakes inhibited root (RDW) and shoot (SDW) dry weight accumulations. For Cu species, maximum negative impact (%) was exhibited by Cu 2+ (RDW:SDW = 94:65) followed by CuO-NPs (RDW:SDW = 78:34) and CuO-BPs (RDW:SDW = 27:22). Aging of NPs/BPs at 1–4 g kg −1 further enhanced the toxic impact of tested materials on biomass accumulations and chlorophyll formation. NPs also induced membrane damage of root tissues and enhanced levels of antioxidant enzymes. The results of this study suggest that care is required when aged metal-oxide NPs of both essential (Zn and Cu) and non-essential (Al and Ti) metals interact with cucumber plants, especially, when they are used for agricultural purposes. Graphical abstract: Image 1 Highlights: Comparative ecotoxicological impacts of metal-oxide species are reported on cucumbers. Effects of non-aged and aged (45 days) particles, and metal ions were investigated. Aged nano metal-oxides had greater phytotoxic effects. Bioaccumulations and translocations of metals in plants were evident by TEM and ICP-MS. Biological attributes were severely reduced by all metal species except bulk of CuO and Al2 O3 .